KEMAMPUAN BERPIKIR KRITIS SISWA MENGGUNAKAN MODEL LEARNING CYCLE MATA PELAJARAN EKONOMI KELAS XI IPA (PEMINATAN) DI SMAN 9 KOTA JAMBI - Lucyana Lucyana; Mayasari Mayasari (Universitas Batanghari Jambi, 2020)
Abstract This study aims to determine the comparison of the use of learning models that are applied (Learning Cycle and Lecture learning models) in economic subjects with government policy material in the economy in class IX science (Specialization) SMAN 9 Jambi City. Based on the results of the study, an analysis was obtained in the control class (the results of the initial pretest were 6 students who graduated and at the final pretest as many as 8 students graduated). Meanwhile, in the experimental class (the results of the initial pretest were 8 students who graduated and in the final pretest as many as 15 students who graduated from KKM). Meanwhile, in the control class post test as many as 23 students did not pass the KKM (67.65%), and only 11 students passed the KKM (32.35%), and in the experimental class post test students who had grades below KKM 8 students (23.53%) and above KKM 26 students (76.47%). Thus, it can be concluded that the Learning Cycle learning model can improve students' critical thinking skills, and help students be more focused in learning compared to the lecture learning model. Because when the teaching and learning process is more centered on the student's role and not dominated by the teacher's role, it is different from the lecture learning model where the teacher plays an active role when learning takes place. Keyword: Critical Thinking Ability, Learning Cycle